Chromosomes Orchestrate Their Own Liberation: Nuclear Envelope Disassembly. Issue 4 (April 2017) - Fernández-Álvarez, Alfonso; Cooper, Julia Promisel
Abstract : The mammalian nuclear division cycle is coordinated with nuclear envelope breakdown (NEBD), in which the entire nuclear envelope (NE) is dissolved to allow chromosomes to access their segregation vehicle, the spindle. In other eukaryotes, complete NEBD is replaced by localized disassembly or remodeling of the NE. Although the molecular mechanisms controlling NE disassembly are incompletely understood, coordinated cycles of modification of specific NE components drive breakdown. Here, we review the current state of knowledge regarding NE disassembly and argue for a role of chromosome–NE contacts in triggering initiation of NE disassembly and thereby, cell division. Trends: NE disassembly is a widely conserved process, with the extent and timing of disassembly varying among species. The LINC complex crosses the NE and associates with specific chromosome regions, particularly centromeres and telomeres, providing a linkage between chromosomes and cytoplasmic elements. Interphase chromosome–LINC interactions constitute a newly recognized cell cycle progression control device. The localized NE recruitment of crucial regulatory factors by specialized chromosomal domains may represent an early-stage NEBD initiator.